2006
DOI: 10.1016/j.visres.2006.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning without feedback in non-stationary contexts: Data and model

Abstract: The role of feedback in perceptual learning is probed in an orientation discrimination experiment under destabilizing non-stationary conditions, and explored in a neural-network model. Experimentally, perceptual learning was examined with periodic alteration of a strong external noise context. The speed of learning, the performance loss at each change in external noise context (switch cost), and the asymptotic accuracy d' without feedback were very similar or identical to those with feedback. However, lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
170
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(183 citation statements)
references
References 57 publications
10
170
0
Order By: Relevance
“…Indeed there is psychophysical evidence that inner reward/feedback can improve performance (Gibson & Gibson, 1955;Herzog & Fahle, 1998;Petrov, Dosher, & Lu, 2006;Shibata, Yamagishi, Ishii, & Kawato, 2009;Sasaki, Nanez, & Watanabe, 2010). For example Shibata et al (2009) found that also a "fake" feedback indicating a larger performance improvement facilitated learning compared with genuine feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed there is psychophysical evidence that inner reward/feedback can improve performance (Gibson & Gibson, 1955;Herzog & Fahle, 1998;Petrov, Dosher, & Lu, 2006;Shibata, Yamagishi, Ishii, & Kawato, 2009;Sasaki, Nanez, & Watanabe, 2010). For example Shibata et al (2009) found that also a "fake" feedback indicating a larger performance improvement facilitated learning compared with genuine feedback.…”
Section: Discussionmentioning
confidence: 99%
“…In perceptual learning paradigms, the subject is presented with a well-defined task explained verbally by the experimenter-orientation discrimination, for example (Fiorentini & Berardi, 1980;Furmanski & Engel, 2000;Petrov, Dosher, & Lu, 2006), texture discrimination (Ahissar & Hochstein, 1997;Karni & Sagi, 1991), motion direction discrimination (Matthews, Liu, Geesaman, & Qian, 1999), or a hyperacuity test (Poggio, Fahle, & Edelman, 1992). After repetitive training (typically including feedback), the subject's performance improves as quantified by threshold or reaction time measures.…”
Section: Classical Perceptual Learning In Humansmentioning
confidence: 99%
“…It "... encompasses parts of the learning process that are independent of conscious forms of learning and involve structural and/or functional changes in the primary sensory cortices" (Fahle and Poggio, 2002). In perceptual learning paradigms, the subject is presented with a well-defined task, such as orientation discrimination (Fiorentini and Berardi, 1980;Furmanski and Engel, 2000;Petrov, Dosher and Lu, 2006), texture discrimination (Ahissar and Hochstein, 1997;Karni and Sagi, 1991), motion direction discrimination (Matthews et al, 1999) or hyperacuity test (Poggio, Fahle and Edelman, 1992) that is explained verbally by the experimenter. After a repetitive training (typically including feedback), the subject's performance improves as quantified by threshold or reaction time measures.…”
Section: Introductionmentioning
confidence: 99%